Hashtags and Hope: Tracing Chinese Digital Spirituality Through #WishMeABabyBoy Trend on Xiaohongshu (Rednote) - Haoyang Zhai (Social Media + Society)
This article examines how digital platforms shape and transform spiritual practices by analyzing the trending “Wish Me A Baby Boy” phenomenon on the Chinese social media platform Xiaohongshu (Rednote). Far from existing as purely personal pursuits, spirituality here emerges as a communal media practice reflecting everyday politics, shaped by cultural traditions, technological affordances, and broader socio-political conditions. Drawing on Chinese traditional practices of wish-making (xu-yuan) and returning the favor (huan-yuan), users adapt these long-standing practices into subtle digital forms, showing ongoing negotiations around cultural values, gender norms, and family expectations. Employing a non-participatory observation and integrating thematic and narrative analysis methods, the study reveals that these online spiritual practices provide unique insights into subtle yet pervasive social tensions in contemporary China, especially those involving fertility pressures, gender expectations, and the lived experiences of ordinary users. In doing so, this research contributes specifically to digital spirituality scholarship by illustrating how culturally marginalized aspirations gain visibility through spiritual expressions and interactions on social media, how platform affordances mediate traditional rituals, and how digital spirituality emerges as a site of ideological negotiation between traditional values (e.g. son preference) and changing gender norms expressed through parody.